2021
DOI: 10.1111/aji.13487
|View full text |Cite
|
Sign up to set email alerts
|

Roles of γδT cells in pregnancy and pregnancy‐related complications

Abstract: A successful pregnancy is a complex and unique process comprised of discrete events, including embryo implantation, placentation, and parturition. To maintain the balance between maternal‐fetal immune tolerance and resistance to infections, the maternal immune system must have a high degree of stage‐dependent plasticity throughout the period of pregnancy. Innate immunity is the frontline force for the establishment of early anti‐infection and tolerance mechanisms in mammals. Belonging to the innate immune syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 95 publications
0
13
0
Order By: Relevance
“… 40 Meanwhile, γδ T cells also have the function of secreting pro‐inflammatory cytokines and cytotoxic molecules, which may exercise their cytotoxic potential in pathological pregnancy. 38 It has been reported that the percentage of granzyme B + γδ T 41 and NKG2D + γδ T 42 cells was significantly higher in peripheral blood lymphocytes of unexplained RIF patients who had failed clinical pregnancy in a subsequent cycle, compared with those who had successful clinical pregnancy. However, the number and function of immune cells in peripheral blood and endometrium are not completely the same or even very different.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“… 40 Meanwhile, γδ T cells also have the function of secreting pro‐inflammatory cytokines and cytotoxic molecules, which may exercise their cytotoxic potential in pathological pregnancy. 38 It has been reported that the percentage of granzyme B + γδ T 41 and NKG2D + γδ T 42 cells was significantly higher in peripheral blood lymphocytes of unexplained RIF patients who had failed clinical pregnancy in a subsequent cycle, compared with those who had successful clinical pregnancy. However, the number and function of immune cells in peripheral blood and endometrium are not completely the same or even very different.…”
Section: Discussionmentioning
confidence: 97%
“…γδ T cells are an essential subgroup of “unconventional” T lymphocytes, which bridge innate and acquired immunity and play multiple roles in the maternal immune system. 38 Compared with non‐pregnant endometrium, the number and percentage of γδ T cells increased significantly during pregnancy. 39 γδ T cells regulate the differentiation and function of NK cells, macrophages, cytotoxic CD8 + T cells, and DC by expressing immunosuppressive molecules such as PD‐1, Tim‐3, CD160 and secreting various anti‐inflammatory cytokines, containing IL‐4, IL‐10, TGF‐β, and IL‐25, and mediate the modulation of T helper‐2 bias in the maternal‐fetal interface to promote the building of immune tolerant microenvironment at the maternal‐fetal interface.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In the process of reproductive immunity, the immunological mechanism that determines the success of pregnancy mainly depends on the interaction between placental trophoblast and decidual immune microenvironment. HLA-E is an immunosuppressive factor, so the decrease of its expression level will weaken the down-regulation of immune response mechanism, leading to the termination of pregnancy ( 83 ).…”
Section: Immunomodulatory Effect Of Hla-ementioning
confidence: 99%